"Mass privatisation and the post-communist mortality crisis": Is there really a relationship? - John S. Earle; Scott Gehlbach (W.E. Upjohn Institute for Employment Research, 2010)
We reexamine the recent, well-publicized claim that 'rapid mass privatisation [of state-owned enterprises] ... was a crucial determinant of differences in adult mortality trends in postcommunist countries' (Stuckler, King and McKee, 2009). Our analysis shows that the estimated correlation of privatization and mortality in country-level data is not robust to recomputing the mass-privatization measure, to assuming a short lag for economic policies to affect mortality, and to controlling for country-specific mortality trends. Further, in an analysis of the determinants of mortality in Russian regions, we find no evidence that privatization increased mortality during the early 1990s. Finally, we reanalyze the relationship between privatization and unemployment in postcommunist countries, showing that there is little support for the proposed mechanism by which privatization might have increased mortality.
Keywords: I18; L33; P2; P31; O57; 330; privatization; mortality; health; shock therapy; unemployment; Eastern Europe; Former Soviet Union; Lancet